1981
DOI: 10.1111/j.1469-8137.1981.tb01739.x
|View full text |Cite
|
Sign up to set email alerts
|

ULTRASTRUCTURAL AND ULTRACYTOCHEMICAL FEATURES OF A GLOMUS TENUIS MYCORRHIZA

Abstract: SUMMARYThe ultrastructural organization and some cytochemical features (protein and polysaccharide distribution) of the mycorrhiza formed by Glomus tenuis in raspberry roots have been investigated. Certain aspects of the fine mycorrhizal endophyte (smaller hyphae, thinner walls, distinct two-layered wall structure following the PATAg test for polysaccharides, complete absence of septa) distinguish it from the coarse vesicular-arbuscular mycorrhizal fungi. The modifications occurring in the host-fungus interfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
1
4

Year Published

1984
1984
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(41 citation statements)
references
References 14 publications
2
34
1
4
Order By: Relevance
“…Arbuscules were uncommon in our Equisetum samples, although many intersections had aseptate hyphae likely to be AM and FE. Like AM, FE can produce arbuscules (Allen et al 2006) which Gianinazzi-Pearson et al (1981) suggested were consistent with a nutrient transfer function. From our 2004 collection on Axel Heiberg, AM arbuscules were This sample was collected from Meadow Lake SK, stained with lactofuchsin and imaged with confocal epifluorescence microscopy.…”
Section: Discussionmentioning
confidence: 90%
“…Arbuscules were uncommon in our Equisetum samples, although many intersections had aseptate hyphae likely to be AM and FE. Like AM, FE can produce arbuscules (Allen et al 2006) which Gianinazzi-Pearson et al (1981) suggested were consistent with a nutrient transfer function. From our 2004 collection on Axel Heiberg, AM arbuscules were This sample was collected from Meadow Lake SK, stained with lactofuchsin and imaged with confocal epifluorescence microscopy.…”
Section: Discussionmentioning
confidence: 90%
“…However, as soon as the hyphae break through the cell wall and come into contact with the host plasma membrane, this membrane elongates and deposits new wall material around the invading fungus (Gianinazzi-Pearson et al 1981). This wall-building activity appears to result from an unspecialized response ofthe host plant cell, designed to accommodate the increasing surface area of its protoplast.…”
Section: Apoplastic and Symplastic Specializations Of The Host Plasmamentioning
confidence: 98%
“…Ultrastructurally, these structures were confirmed in this study to be intrahyphal hyphae. The formation of hyphae within existing hyphae has been reported in a number of fungi (Chan and Stephen, 1967;Calonge, 1968), including VAM fungi (Tommerup and Abbott, 1981;Gianinazzi-Pearson et al, 1981;Lim et al, 1983). The initiation of intrahyphal hyphae has been related, in many instances, to microaerobic growth conditions of fungi in solid and liquid media (Miller and Anderson, 1961;Calonge, 1968;Kendrick and Molnar, 1968), and increasing age of the fungus (Chan and Stephen, 1967), or has been identified as a normal feature of growth (Hammill, 1972).…”
Section: Discussionmentioning
confidence: 95%